تأثير الأجهزة الدبلوماسية على صادرات الجزائر للفترة 2009/2018 بإستخدام نموذج الجاذبية - شرع, يوسف; شرع, نورة (جامعة الوادي - University of Eloued, 2022)
الجزائر دولة كباقي دول العالم تسعى لزيادة صادراتها بإتباع عدة سياسات من بينها المعاهدات و الاتفاقيات الدولية من خلال أجهزتها الدبلوماسية. يهدف هذا إلى معرفة مدى مساهمة الأجهزة الدبلوماسية في زيادة الصادرات الجزائرية مع أهم شركائها التجاريين. وكانت نتيجة الدراسة أنه كلما زاد التمثيل الدبلوماسي للبلدان الشريك ذات الدخل المرتفع في الجزائر بوحدة واحدة كلما زاد حجم الصادرات الجزائرية بـ 1.88 وحدة. أما بالنسبة للتمثيل الدبلوماسي للجزائر في البلدان الشريك ذات الدخل المرتفع لم يكن له أي تأثير. و بالنسبة للدول الشريكة ذات الدخل المتوسط و المنخفض فكلما زاد التمثيل الدبلوماسي للجزائر في هذه الدول بوحدة واحدة كلما زاد حجم الصادرات الجزائرية بـ 1.46 وحدة ؛ أما بالنسبة للتمثيل الدبلوماسي للبلدان الشريك في الجزائر لم يكن لها أي تأثير على صادرات الجزائر. Similar to other countries worldwide, Algeriaseeks to increase its exports and develops its economy by signing newInternational treaties and conventions through its diplomatic agencies and international influence. This research aims to assess the extent of the diplomatic agencies contribution in increasing Algerian exports with its most importantbusiness partners. The result of the study showed that1 unit increase in our high income partner countriesdiplomacy representation leads to an increase in the volume of Algerian exports by 1.88 units whereas, there have been no influence found in the increase of Algerian diplomacy representation in these countries. Further investigation for our partner countries having low and medium incomeshowedthat anincrease by 1.46 units in the volume of Algerian exports results when the Algerian diplomacy representation in these countries increases by 1 unit.
The impact of diplomatic services on Algeria's exports for the period 2009/2018 using the gravity model
مقال
Keywords: اجهزة دبلوماسية، بعثات دبلوماسية، صادرات، نموذج الجاذبية.